MAKNA KARIKATUR HABIB RIZIEQ PADA COVER MAJALAH TEMPO: Analisis Semiotika Charles Sanders Pierce - Muliadi; Ulfa Khairina; Adrianda, Irsan (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
This research examines caricature of Habib Rizieq on the cover Tempo magazine. The focus of this research is to examine how the meaning of Habib Rizieq's caricature with description qualitative methods. The theoritical review used is Charles Sander Pierce's semiotics, namely by looking at the meaning of the sign (icon, index, and symbol), object and interpretant. This study examine 2 (two) caricatures that were studied from 23-29 July 2018 edition regarding the source of pronography. So it can be concluded that the researchers interpretation assessed that the two caricatures were related to the events that occured.